Detecting Differences in Communication During Two Types of Patient Handovers: A Linguistic Construct Categorization Approach. (September 2014) - Woods, Zachary; Hilligoss, Brian; Duchon, Andrew; Beecroft, Nicholas; Patterson, Emily S.
Patient handovers are a critical point in the patient care process. Software to identify differences in communication content and strategies across different types of patient handovers could be helpful in customizing physician training programs. To determine whether there were differences, Linguistic Inquiry and Word Count (LIWC) software was used. The primary measure was the LIWC output score, which is the frequency of mention of words in a construct category divided by the total number of words in the handover transcript. Two types of constructs were investigated: 1) content, which included name/age, care plan, prognosis, and family, and 2) strategy, which included questioning and collaborative cross-checks. We hypothesized that the Emergency Department (ED) to hospital transfer compared to Intensive Care Unit (ICU) sign-outs would have more discussion of family and less of the patient's prognosis, as well as more collaborative cross-checks. A two-tailed t-test was used to detect differences. One hypothesis was confirmed, that there was less discussion of prognosis in the ED as compared to the ICU handover. Unexpected findings were less discussion of the care plan and more questioning in the ED as compared to the ICU handover. Findings confirm that both communication content and strategies are different for the two types of patient handovers and that an automated analysis approach can detect differences across a set of handover transcripts.